CHARACTERISTICS OF THE TYPES OF LEFT VENTRICULAR REMODELING AMONG WORKING AGE MEN WITH ISCHEMIC HEART DISEASE, LIVING IN ONE OF THE MOUNTAIN REGIONS OF AZERBAIJAN - N. R. Ismaylova; F. A. Kuliev; A. F. Zeynalov (Столичная издательская компания, 2015)
Aim. To evaluate the rate of left ventricular hypertrophy (LVH) and left ventricular (LV) geometry types in ischemic heart disease (IHD) among men of working age in one of the mountain regions of Azerbaijan. Material and methods. A representative sample of the informal working age men population living in the foothills and midlands of theRepublic ofAzerbaijan was examined. Representative sample was formed by the method of random numbers. Strictly standardized survey methods and evaluation criteria recommended by WHO for epidemiological studies were used. Echocardiography with evaluation of the heart morphological parameters was performed in all the subjects. Results. The prevalence of LVH in IHD patients was 68.8% [based on the calculation ofLV mass (LVM) and the LVM index (LVMI)]. The most reliable LVH detection was observed with calculation of three indexes LVMI, LVMI/height and LVM/height2,7. The least reliable LVH detection was observed with use only one index LVM/ height2,7. Normal LV geometry was registered in 20 (21.5%) patients with IHD,LV concentric remodeling in 18 (19.4%), concentric LVH in 23 (24.7%), and eccentric LVH in 32 (34.4%) patients. Conclusion. The results of the study show significant prevalence of both LVH and adverse types ofLV remodeling in this population. This calls for further research to study the causes of revealed epidemiological situation.